ANALISIS ERGONOMI BEBAN KERJA TERHADAP KELELAHAN KERJA PADA PEKERJA MANUAL BATU BATA DENGAN REGRESI LINIER BERGANDA BERBASIS WEB - Junaini; Yano Hurung Anoi; Yunanri W (STTI Bontang, 2021)
Small industry has a big role in encouraging development in areas, especially rural areas, which cannot be separated from national development in accordance with regional autonomy and regional aspirations. One of the small industries to fulfill development is the brick-making industry manually because it still uses a simple process in its production. Manual brick making cannot be separated from the risks that will arise for workers, one of the risks is fatigue due to the workload carried out in the process of making bricks repeatedly, the workload can be in the form of physical loads or mental loads. Fatigue from work will reduce performance and increase the rate of work errors. Increasing work errors will provide opportunities for work accidents. From this it is necessary to measure workload on work fatigue from the results of the ergonomic analysis of brickwork manual workers with Linear Regression with web-based programming. Each worker will be recorded based on the category Initial Pulse, Work Rate, Body Weight, Blood Pressure, Height, Age, as well as several questions to workers needed to measure the workload against work fatigue. Questions about Activity Weakness and Physical Fatigue in a span of days (Very Often, Often, Sometimes, Never; to each worker. The conclusion from the results of the workload analysis has an influence on fatigue of work in making bricks manually, namely Normal or Not Fatigue 6 workers , and Needs Improvement 9 workers with the percentage classification of Cardiovascular Load (CVL) is 40% and 60%.